ANALISIS PERBEDAAN RETURN DAN RISIKO SERTA PENGARUH KINERJA KEUANGAN TERHADAP RETURN DAN RISIKO PADA SAHAM JAKARTA ISLAMIC INDEX DAN SAHAM NON JAKARTA ISLAMIC INDEX PERIODE 2007-2011 - , Siska Priyandani Yudowati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Number of issuers in the list of Islamic securities in 2007 to 2012 increase every year thus increasing the market capitalization of Islamic securities. Increased market capitalization is reflected in the growing volume of transactions that Islamic stock index represented by Jakarta Islamic Index signals that investors are starting to believe in investment through Islamic stock. Election syariah stock due to investors' perception that the operations of Islamic issuers incorporated in the Jakarta Islamic Index stock groups classified as more secure so that its performance tends to be more stable and the profit generated on average has increased every year. This research is to reveal the existence of differences in risk and stock returns between issuers/companies are categorized in the group with the Jakarta Islamic Index and stock issuers/companies are not categorized in stock Jakarta Islamic Index (non JII) during the period of 2007-2011, analyzed using the approach financial ratios are the Current Ratio, Debt Ratio, ROE, Price to Book and Operating Profit Margin to determine whether the effect on the financial performance of both stock returns and stock risk groups Jakarta Islamic Index and the stock instead of stock Jakarta Islamic Index during the period 2007 -2011. Object of this study is stock belonging to the group with the Jakarta Islamic Index stock shares instead of groups Jakarta Islamic Index (non JII) during the period 2007-2011. Analysis of the data in this study using the Independent T test and Multiple Linear Regression. Results of the analysis revealed no difference in stock returns,but there is a difference in risk between groups Jakarta Islamic Index stocks with stock instead of groups Jakarta Islamic Index (non JII) during the period of 2007-2011. The financial performance of the company through the Current Ratio, Debt Ratio, ROE, Price to Book and Operating Profit Margin together have an influence on Average Equity Return JII only by 18.6 % and Return on Average Equity non JII only by 13.3 %. While the risk of both JII stock and non JII stock is not influenced by the company's financial performance. Price to Book has a positive influence on Average Equity Return JII. Debt Ratio has a negative effect or the opposite and Price to Book has a positive influence on non JII Average Stock Return. ROE has a positive influence and Price to Book has a negative or opposite effect on the risk (beta coefficient) JII stocks.